PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE FIRING LINE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIISMPN17 PADANG - Gusliani, Rina; Harisman, Yulyanti; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACT The background of this research was by the lack of student participation in teaching learning process grouply. The student  did not have an effort to practise individually, the students understanding of mathematical concept still low.  It can be seen at the result students mathematic at the eight grade of student SMPN 17 Padang 2013 / 2014. This was an experimental reseach, applied random to subjek. The population was  eight grade student of SMPN 17 Padang 2013 / 2014, consist of eight class. Technique of data collection was  random, VIII-7 as experimental and VIII-8 as control class. Instrument in this research was understanding of mathematical concept in essay form. Based on the data analisys known that both of class homogeneous and have  normal distribution. The hypothesis was accepted. Can concluded that understanding of mathematical concept by applied active lerning The Firing Line  type better than appllied conventional learning at the eight grade students SMPN 17 Padang.